2019
DOI: 10.1038/s41598-019-38848-5
|View full text |Cite|
|
Sign up to set email alerts
|

Heart beat but not respiration is the main driving force of the systemic venous return in the Fontan circulation

Abstract: The Fontan procedure provides relief from cyanosis in patients with univentricular hearts. A major clinical unmet need is to understand whether the venous flow patterns of the Fontan circulation lead to the development of congestive hepatopathy and other life-threatening complications. Currently, there is no consensus on whether heart beat or respiration is the main driving force of venous return and which one affects the periodic flow changes for the most (i. e., pulsatility). The present study, for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Respiratory-resolved analyses suggested increased peak velocity and net flow in the SVC and decreased peak and net flow in the IVC at Resp4. Although the influence of respiration on cardiopulmonary flow has been investigated for decades, the exact relationship is still unclear (1,23,24). The varying effects of respiration reported in this study and in previous studies suggest that studies with more respiratory bins are warranted.…”
Section: Discussionmentioning
confidence: 58%
“…Respiratory-resolved analyses suggested increased peak velocity and net flow in the SVC and decreased peak and net flow in the IVC at Resp4. Although the influence of respiration on cardiopulmonary flow has been investigated for decades, the exact relationship is still unclear (1,23,24). The varying effects of respiration reported in this study and in previous studies suggest that studies with more respiratory bins are warranted.…”
Section: Discussionmentioning
confidence: 58%
“…In this case study, we present a lumped‐parameter representation of the Fontan circulation to illustrate the role that respiration alone plays on the hemodynamics of venous return, as recently demonstrated in vivo. [ 84 ] This work concluded that breathing, rather than the pumping action of the heart, is responsible for the flow characteristics observed in the IVC in this patient population. By comparing the IVC hemodynamics obtained in silico, we aim to further demonstrate the versatility of our proposed platform.…”
Section: Resultsmentioning
confidence: 95%
“…[ 80 ] Although this surgery prolongs life, hemodynamic abnormalities result from this procedure, and the resulting single ventricle physiology, including low pulsatile flow within the inferior vena cava (IVC) and elevated hepatic venous pressures, which can lead to a host of long‐term morbidities and mortality. [ 81–84 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations